73 IS METABOLIC SYNDROME AN INDEPENDENT RISK FACTOR FOR CORONARY ARTERY DISEASE?. (1st March 2006) - Weissman, A. J.; Bhatti, T. K.; Hersh, D.; Panagopoulos, G.; Jimenez, M.; Coplan, N. L.
Abstract : Introduction: Metabolic syndrome consists of a constellation of metabolic abnormalities that include glucose intolerance, obesity, elevated blood pressure, and dyslipidemia. There are conflicting results in the medical literature as to whether the components of the metabolic syndrome, taken together or individually, can improve existing formulas such as the Framingham risk score for estimating the 10-year risk for cardiovascular disease. The purpose of this study was to determine if the metabolic syndrome is an independent risk factor for the presence of coronary artery disease (CAD). Methods: A total of 174 patients with no known history of CAD who presented for elective cardiac catheterization were included in the study. These patients were evaluated for the presence (M+) or absence (M-) of the metabolic syndrome using the NCEP-ATP III criteria; CAD was defined as the presence of at least 70% stenosis in one of the three major coronary vessels or one of their significant branches or 50% stenosis in the left main coronary artery. The relationship between the metabolic syndrome and the presence of CAD was assessed by using the Pearson chi-square test. Results: Metabolic syndrome was present in 95/174 patients (54.6%), and M+ was significantly more likely to have CAD than M- (43% vs 28%, p = .036). There was no significant difference between M+/M- with regard to the mean Framingham risk score or for age, tobacco use, or family history of CAD; there was a significantly increased prevalence of DM (defined as fasting blood sugar > 126 mg/dL or DM Rx) in the M+ group ( p < .01). Given that DM is a coronary risk equivalent, subgroups with DM and without DM were evaluated separately: Conclusion: Metabolic syndrome, independent of diabetes mellitus, is not a risk factor for obstructive coronary artery disease.